The effect of COVID-19 pandemic on college enrollment: How has enrollment in criminal justice programs been affected by the pandemic in comparison to other college programs - Korotchenko, Stan; Dobbs, Rhonda (Frontiers in Education, 2023)
The COVID-19 pandemic has affected various aspects of our lives. For many, it has affected their ability to attend school. While some have switched to online classes, others have had to drop or delay college until later. Using official enrollment data for 12 public universities in the State of Texas, this study explores the impact the COVID-19 pandemic has had on student enrollment in criminal justice programs. A series of statistical techniques, including t-tests comparing pre- and post-pandemic enrollment numbers and panel data analysis models, are utilized to investigate the trends and changes in the program enrollments between 2009 and 2021. While in alignment with the existing research on the effect of the COVID-19 pandemic on college enrollment in general the authors have found a negative statistically significant effect of the pandemic on total college enrollment for all universities in the sample, no statistically significant effect of the pandemic was found on enrollment in criminal justice programs at 12 public universities. The effect was also non-existent for engineering and all social science programs combined. In contrast to all other programs studied herein, enrollment in natural science programs was found to be positively associated with the pandemic. The authors offer an explanation for these findings as well as suggest ideas for future research.